Accreditation For The Quality Of Higher Education Graduates - Rizki, Fitri; Rizky Khairunnisa; Susiani (MIND Jurnal Ilmu Pendidikan Dan Budaya, 2024)
Higher Education institutions are mostly work-force providers to Industries, private-owned and state-owned and even Government Departments. Due to the fact, the quality of Higher Education Degree should be in compliance with the requirement of these organizations. To achieve the needs, the country has conducted an accreditation that suggests three tools to the institutions to make sure that the higher education institutions have the quality- improving tools to gain the quality of the degrees, that the organizations need. to the recruit as needed by the organizations themselves. Institutions’ understanding the link between quality improvement and profits will improve customers’ satisfaction, competitiveness and financial performance.